KESALAHAN BERBAHASA INDONESIA PADA SURAT DINAS DESA BATAN SEBAGAI MATERI AJAR BAHASA INDONESIA DI SMP - Yolanda Agnes Aldema; Edy Suryanto; Raheni Suhita (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
This study aims to describe: (1) the forms of misuse of spelling on official letters in and out of the Village Office of Batan Village; (2) a form of error in the choice of words on official letters in and out of the Batan Village Office; (3) the form of misuse of the sentence on official letters in and out of the Village Office of Batan Village; and (4) the relevance of the findings of the analysis of errors in the use of Indonesian with learning letters in junior high school. The method used is qualitative descriptive. The data source used is in the form of documents and informants. The sampling technique uses purposive sampling. Data collection techniques use document analysis and interview techniques. The validity of the data is done by theory triangulation and source triangulation. Data analysis is using interactive analysis. The results of the study showed: (1) there were spelling errors in the official letter of entry and exit in the Village of Batan as many as 1,171 errors, among the three types of errors in spelling, capital letters errors had the most frequency followed by word punctuation and writing errors; (2) there were 273 errors in the official letter of entry and exit in the Village of Batan. Among the three types of diction errors, the savings error has the highest number of errors followed by errors in accuracy and rigidity; (3) there were 142 mistakes in sentence in the official letter of entry and exit in the Village of Batan Village. Among the three types of errors in the sentence, the error of the unitary arrangement has the most frequency followed by logical errors and politeness; (4) the findings of the analysis can be evaluated on the learning of letters in junior high school class VII, KD 3.11 and 4.11 and KD 3.12 and KD 4.12.